ASSESSING THE IMPACT OF FOREIGN DIRECT INVESTMENT ON ARGENTINA’S STOCK MARKET CAPITALIZATION - Bakhtiar, Adnan Taleb (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
This study examines dynamic relationships between foreign direct investments (FDI) and stock market value in Argentina from 1998 to 2025. The relevant theoretical structure and drawing on empirical data appoints a semi-logical authoritative model to investigate the effects of FDI and economic development (GNP). Conclusions suggest that the FDI and GDP have significant positive effects, while inflation seems statistically insignificant. The study provides significant implications for political decision-makers who promote capital market development through foreign investments and macroeconomic stability.